Polychlorinated biphenyls and organochlorine pesticides in River Brahmaputra from the outer Himalayan Range and River Hooghly emptying into the Bay of Bengal: Occurrence, sources and ecotoxicological risk assessment. (December 2016) - Chakraborty, Paromita; Khuman, Sanjenbam Nirmala; Selvaraj, Sakthivel; Sampath, Srimurali; Devi, Ningombam Linthoingambi; Bang, John J.; Katsoyiannis, Athanasios
Abstract: River Brahmaputra (RB) from the outer Himalayan Range and River Hooghly (RH), a distributary of River Ganga, are the two largest transboundary perennial rivers supplying freshwater to the northeastern and eastern states of India. Given the history of extensive usage of organochlorine pesticides and increasing industrialization along the banks of these rivers we investigated selected organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) in the surface water of River Brahmaputra and River Hooghly. Geomean of ΣOCPs (53 ng L −1 ) and Σ19 PCBs (108 ng L −1 ) was higher in RH compared with geomean of ΣOCPs (24 ng L −1 ) and Σ19 PCBs (77 ng L −1 ) in RB. Among OCPs, γ -HCH showed maximum detection frequency in both the rivers reflecting ongoing lindane usage. DDT and endosulfan residues were observed at specific locations where past or ongoing sources exist. Elevated concentrations of heavier congeners (penta-hepta) were observed in those sites along RH where port and industrial activities were prevalent including informal electronic waste scrap processing units. Furthermore along River Hooghly PCB-126 was high in the suburban industrial belt of Howrah district. PCBs were found to be ubiquitously distributed in RB. Atmospheric transport of tri- and tetra-PCB congeners from the primary source regions might be a major contributor for PCBs in RB. Heavier congeners (penta-nona) in the urban centers of RB were likely due to industrial wastewater runoff from the oil refineries in the Brahmaputra valley. Σ19 PCBs concentrations in this study exceeded the USEPA recommended limit for freshwater. Ecotoxicological risk assessment showed the possibility of adverse impact on the organisms in the lower trophic level due to DDT and lindane contamination. Impact of endosulfan on fishes might be of considerable concern for aquatic environment. Graphical abstract: Highlights: Waste discharge from industrial or port activities were suspected sources for heavier congeners and dl-PCBs in River Hooghly. Long range atmospheric transport could be a major contributor for PCBs in River Brahmaputra along the outer Himalayan Range. Residues of DDT and lindane showed risk for lower trophic organisms and endosulfan affected fishes including edible species.